Plan de ordenamiento turístico para el desarrollo de las parroquias Chone y Santa Rita de la Provincia de Manabí - Solís Solórzano, Cristhian Bryan (2023)
The research was developed with the objective of developing a tourism management plan that contributes to the development of the urban parishes of Chone and Santa Rita in the province of Manabí. The study was exploratory in nature, with a mixed approach, developed from a documentary-bibliographical and field investigation; composed of four phases: multidimensional characterization of the territory, evaluation of tourism resources, systematization of tourism problems and potentialities, and design of the tourism management plan; Obtaining the following results: most of its economy is based on agriculture and livestock, in the tourist field there are problems when accessing the attractions, there is no adequate signage, entrepreneurs do not receive training. When evaluating the resources, it was verified that the Santa Rita parish has great potential for the development of agrotourism, it has waterfalls and is more directed towards rural tourism; Chone parish stands out for cultural and heritage tourism. Through the systematization of the problems, it was possible to find out that the residents of the communities do not work together with the local governance authorities, because a conflict of interest persists; however, they are ready to work to strengthen tourism and improve the economy of the sector. Finally, the Territorial Development and Planning Plan was structured, defining the corresponding zoning of each parish, strategic actions, programs and projects were established aimed at improving tourism, in order to contribute to the development of tourism in the area.